Learning Practices Method Effective to Increase Nurses Knowledge on Preceptorship Training - Mona Saparwati; Achmad Syaifudin; Tri Ismu Pujiyanto (Indonesian Journal of Global Health Research, 2021)
Nursing Manager is required to have the responsibility and able to perform quality nursing management so as to produce quality nursing services. In order to implement the management of care in the inpatient room, a nurse who meets the standard of the role of the care manager as well as able to transfer the skill and experience to the junior Nurse or Nursing students who are performing the practice of nursing clinics. Preceptorship Training is an educational process that emphasizes psychomotor aspect although it is based on knowledge and attitude with more interactive teaching method and shorter period of time compared to formal education which gives opportunity for practitioners in giving support to students in understanding their role and relationship welfare. This study aims to analyze the effectiveness of learning media practicum of nurse knowledge about clinical guidance Preseptorship method. Research design Pre-test and Post Test with control group design, where the treatment group was trained with lecture, discussion and practical methods, while the control group was trained with lecture and discussion methods only. Data analysis used the Wilcoxon test. There was a significant difference between the intervention group and the control group after the training at hospital. Preceptorship training with role playing practice method effective improves the knowledge score of nurses at hospital. Suggestions in this study include applying the results of the training on the process of clinical counseling method of Preseptorship thoroughly in hospital, improving the supervision of prescribing clinical methods preceptorship and helping improve the role of nurse as a preceptor in the clinic.